Isolation and identification of Saprolegnia spp. from infected sturgeon caviar - Ekaterina P. Anokhina; Anna A. Tolkacheva; Nina A. Pryakhina; Mikhail Yu. Syromyatnikov; Olga S. Korneeva (Acta Biologica Sibirica, 2023)
Saprolegniosis is considered one of the most common fungal diseases in freshwater aquaculture, affecting eggs and fish of all ages, and is causing great economic losses worldwide. In sturgeon aquaculture, highest harm is caused by caviar saprolegniosis (byssus), a mycotic disease of caviar, which is characterized by damage through saprolegnium fungi during hatchery incubation. The main infectious agents are aquatic mold fungi of the genus Saprolegnia spp. A sample of water mold was isolated from infected eggs of a hybrid of Russian sturgeon (Acipenser gueldenstaedtii) with kaluga (Huso dauricus) with characteristic signs of the disease. Microscopic examination of an isolated oomycete revealed morphological features characteristic of Saprolegnia spp., but no oogonia or antheridia were found, which complicates further species identification. To identify the isolated pathogen, molecular tools such as PCR and sequencing of a DNA section including 18S rRNA, ITS1, 5.8S rRNA, ITS2 and 28S rRNA were used to distinguish between different species of aquatic molds. Analysis of the obtained nucleotide sequence showed more than 99% identity with the previously known DNA sequences of S. parasitica. According to the results of phylogenetic analysis, the obtained nucleotide sequence was in the same group with the known sequences of S. parasitica and separated from other species belonging to S. ferax, S. diclina, S. delica, and S. australis.